SEKTOR ENERGI ISIS SEBAGAI MATERIAL CAPABILITIES DALAM MENDIRIKAN ISLAMIC STATE BERDASARKAN PENDEKATAN ROBERT W. COX - Febrianto, Faris (Department of International Relations Universitas Pertamina, 2021)
ISIS is a terrorist group that controls parts of Iraq and Syria which targets the energy sector in various attacks to control an energy source. Meanwhile, ISIS uses the energy sector to encourage its financial sector to be able to establish and maintain the Islamic State. In this article, the author uses a qualitative method that relies on internet-based research as a data collection technique and uses a Robert W. Cox approach for data analysis. This article aims to analyze the energy sector controlled by ISIS as material capabilities in realizing the Islamic State based on the approach of Robert W. Cox. The author finds that ISIS has control over oil refineries and natural gas fields in its territory so that it makes a large contribution to ISIS finances. The energy sector has also resulted in ISIS being able to establish the Islamic State and supply its military forces to defend it. Through the approach of Robert W. Cox, it can be concluded that the energy sector is a material capability owned by ISIS to build power and the Islamic State.